2015
DOI: 10.1038/ncomms8202
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging of a three-component ordered actin disassembly mechanism

Abstract: Summary The mechanisms by which cells destabilize and rapidly disassemble filamentous actin networks have remained elusive; however, Coronin, Cofilin, and AIP1 have been implicated in this process. Here, using multi-wavelength single molecule fluorescence imaging, we show that mammalian Cor1B, Cof1, and AIP1 work in concert through a temporally ordered pathway to induce highly efficient severing and disassembly of actin filaments. Cor1B binds to filaments first, and dramatically accelerates the subsequent bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
151
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(170 citation statements)
references
References 51 publications
18
151
1
Order By: Relevance
“…In addition, AIP1 remains bound transiently to severed filaments (Fig. 7, top right) and contributes to capping when coronin is present (20), but the effect of pH on this process remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AIP1 remains bound transiently to severed filaments (Fig. 7, top right) and contributes to capping when coronin is present (20), but the effect of pH on this process remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…ADF/Cofilins bind to G-actin between subdomains I and III, and strongly inhibit nucleotide exchange on actin monomers [21]. Real time imaging using multi-wavelength Total Internal Reflection Fluorescence (TIRF) microscopy has shown that yeast Cofilin and human Cof1 bind actin filaments in a cooperative manner, and induce severing at the boundaries between bare and decorated segments [2224]. ADF/Cofilin binding also alters the structure and mechanical properties of actin filaments [21, 22, 2529], and induces the release of cations to ‘soften’ F-actin, creating mechanical discontinuities that induce fragmentation [27].…”
Section: Introductionmentioning
confidence: 99%
“…8 B, middle and right). We extended our analysis to two additional potential binding partners of myosin IIIa in cochlear hair bundles: coronin-1a (found with the PPI Finder tool; He et al, 2009), an actin-binding protein that promotes the cofilinmediated severing of actin filaments (Jansen et al, 2015), and espin-like, an espin paralogue similar in structure to espin-1 (Shin et al, 2013;Zheng et al, 2014). Both coronin-1 and espin-like had similar locations at the tips of cochlear stereocilia in the presence and in the absence of class III myosins (Fig.…”
Section: Cochlear Hair Cells Of Myo3a −/− Myo3b −/− Mice Display Robumentioning
confidence: 99%